RUH ISLAM DALAM â€œWADAGâ€ LOKAL MADURA: Kasus â€œTanean Lanjengâ€ - Susanto, Edi (KARSA: Journal of Social and Islamic Culture)
AbstracThis paper presents an interaction between Islam and local culture of Madurese. The locus of the study has been Taneyan Lanjeng. It is viewed as a total reflection of Madurese in applying the thought of Islam, thus it is well-off Islamic values. The digging of meaning behind Taneyan Lanjeng, as cultural metaphor, is necessaity to realize Islam as an environment-care religion. The term of environment covers social, cultural and perhaps natural environments Kata-kata kunciruh Islam. tanèyan lanjèng